On the road with Charles Kuralt - Kuralt, Charles, 1934-1997. (New York : Putnam, 1985)
Contains the best of his pieces from "Crossroads," the "American Parade," and "On the Road."
Keywords: United States -- Description and travel; United States -- Social life and customs -- 1945-1970.; United States -- Social life and customs -- 1971-; United States -- Civilization -- 20th century